1977
DOI: 10.1177/105960117700200405
|View full text |Cite
|
Sign up to set email alerts
|

Organization Development Techniques: Their Impact on Change

Abstract: Organization development (OD), as an applied arm of the field of organizational behavior, purports to facilitate organizational change through the use of a variety of change interventions. Its proponents feel that the tools and techniques of OD can improve an organization's problem-solving ability, increase its ability to adapt to rapid societal change, and provide managers an updated set of concepts and methods for managing their organizations. This article reviews and evaluates the research on the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…They summarized ten survey feedback intervention studies and concluded that such can have positive effects on the attitudes of those involved. Shortly after, Margulies et al (1977) summarized six studies relevant to this type of OD intervention and concluded that more research was needed on this technique to understand under which circumstances it produces the most benefits. A few years later, Porras and Berg (1978) and Porras (1979) reviewed four survey feedback intervention studies as one of several different OD techniques, but could not find superiority of this technique over others.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They summarized ten survey feedback intervention studies and concluded that such can have positive effects on the attitudes of those involved. Shortly after, Margulies et al (1977) summarized six studies relevant to this type of OD intervention and concluded that more research was needed on this technique to understand under which circumstances it produces the most benefits. A few years later, Porras and Berg (1978) and Porras (1979) reviewed four survey feedback intervention studies as one of several different OD techniques, but could not find superiority of this technique over others.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Margulies etal. [2] analyzed 30 studies and found positive result in over 70% of them. Dunn and Swierczek [3] examined 67 cases and found positive gains in almost 70% of the time.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Many case studies of successful interventions have been reported in such journals as Group and Organization Studies and the Journal of Applied Behavioral Science. Also, a number of empirical studies of OD processes (for reviews, see Porras, 1979;Margulies, Wright, & Scholl, 1977) conclude that a wellrun OD intervention can aid an organization in terms of such variables as member satisfaction, teamwork, communications, conflict resolution, from which to choose (e.g., intergroup development, team building, survey feedback, and structural change), and the development of a model for determining the appropriate intervention strategy to employ in a particular situation has not been forthcoming. Various authors have suggested different variables to consider in the process of selecting an intervention strategy; for example, commitment of top management, existence of slack resources, existence of political support (Beer, 1980), or problem behaviors and their causes or precursors (Bowers, Franklin, & Pecorella, 1975).…”
mentioning
confidence: 98%
“…Various authors have suggested different variables to consider in the process of selecting an intervention strategy; for example, commitment of top management, existence of slack resources, existence of political support (Beer, 1980), or problem behaviors and their causes or precursors (Bowers, Franklin, & Pecorella, 1975). Porras (1979), Margulies et al (1977), and Bowers (1973) have reviewed numerous OD studies and attempted to provide generalizations regarding the types of variables affected by various intervention strategies. However, these reviews do not provide a clear model to guide the decision process of selecting an appropriate strategy in a given situation.…”
mentioning
confidence: 98%